An examination of the Portuguese banking sector crisis - Pereira, V. (2017)
The purpose of this research is to analyse the trends in data from monetary financial institutions (MFIs) in Portugal compared to the Euro Area. The analysis principally focuses on the period after the subprime crisis, which started in 2007 in the USA. Moreover, this article exposes some interesting data about corporate governance in Portuguese banks (e.g. governance model, gender, board dimension, executive compensation, board members’ qualifications). Of particular note is the fact that after the bail-out of Portugal in 2011, the Portuguese banking system started a process of downsizing evidenced not only by the reduction in the number of branches but also cuts to human resources. In terms of board characteristics, it is evident that the majority of Portuguese banks use the Latin model of corporate governance. Furthermore, only a small number of Portuguese banks are listed (a total of three were registered). Another aspect of note is the limited presence of women on boards of directors.